Exploring storytelling as a method to build local knowledge : (Re)thinking sexuality education with rural women in Sucre, Bolivia from a feminist decolonial perspective - Pernthaler, Magdalena (2022)
Although most SRH interventions today are based on a human rights approach, many of them are inherently Eurocentric, modeled around the needs of privileged Global North women and do not acknowledge the experiences and expectations of the target population. As a result, SRH programs commonly fail to reach the most marginalized populations such as the research participants to this study, 14 women who have migrated from remote rural communities to the city of Sucre, Bolivia. In an attempt to question the imposition of allegedly universal SRH programs on women like the research participants, this thesis aims to explore how research on SRH could be conducted from a feminist decolonial perspective. Given the central role methodology plays in such an endeavour, one of the main objectives of this thesis is therefore to examine how storytelling can be used as a method to build local knowledge based on which decolonial SRH programs could be developed. Due to my own positionality as a privileged white woman from the Global North, core to these methodological considerations is the analysis of the role of outside researchers in decolonial research. The other key objective of this thesis project is to provide the research participants a space to share their stories, connect with each other and collectively contribute to the diversification of knowledge production. Regarding the specific research method, five storytelling sessions were carried out. During these sessions which revolved around different theme blocks connected to sexuality and reproduction, the participating women were invited to share their experiences and together create an alternative, collective story. The initial aim of these sessions was to build a body of knowledge which would facilitate learning about the women’s own conceptualizations of issues related to SRH. However, eventually the outcome was much broader, producing rich life histories which help to gain a more holistic understanding of the specific needs, experiences, and expectations of the women in regard to their SRH. Concerning the results of this study, the positive feedback from the research participants suggests that building localized SRH programs through a bottom-up approach holds great potential to advance the SRH of the most marginalized. At the same time, informing the methodology with a feminist decolonial perspective does not only open a space to question Eurocentric structures underlying SRH programs but also to tackle patriarchal and oppressive structures impeding women’s SRH within communities.